The ECB Single Supervisory Mechanism: Effects on bank performance and capital requirements - Burkhard Raunig; Michael Sigmund (Oesterreichische Nationalbank (OeNB), 2022)
Under the Single Supervisory Mechanism (SSM) introduced in 2014, the European Central Bank directly supervises significant euro area banks, which hold about 82% of total banking assets. We find that this important supervisory change has positive effects on the return on assets and the return on risk-weighted assets of SSM banks without increasing the risk weights used to calculate regulatory capital. Our findings indicate that these effects result from better risk management and increased confidence in the soundness of SSM banks. Our results therefore suggest that the SSM has strengthened the resilience of the euro area banking system.
Keywords: 330; ECB Single Supervisory Mechanism; bank profitability; capital requirements; risk-weighted assets